2014
DOI: 10.1071/an14535
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of energy balance data from growing cattle using parametric and non-parametric modelling

Abstract: Abstract. Linear and non-linear models have been extensively utilised for the estimation of net and metabolisable energy requirements and for the estimation of the efficiencies of utilising dietary energy for maintenance and tissue gain. In growing animals, biological principles imply that energy retention rate is non-linearly related to the energy intake level because successive increments in energy intake above maintenance result in diminishing returns for tissue energy accretion. Heat production in growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A k m > 1.00 means something is gotten for nothing and is necessarily prohibited by the first law. Estimates of k m reported by Baldwin (1995) and Moraes et al (2014) are similar to HE from bond breakage, such as glycogen → glucose, and may only partially represent metabolic processes associated with maintenance. Old and Garrett (1987) described the relationship between RE and MEI as a quadratic function; estimates of ME m were 0.0953 Mcal ME/ BW 0.750 × d −1 (Hereford steers) and 0.100 Mcal ME/BW 0.750 × d −1 (Charolais steers).…”
Section: Variability In K Mmentioning
confidence: 86%
See 3 more Smart Citations
“…A k m > 1.00 means something is gotten for nothing and is necessarily prohibited by the first law. Estimates of k m reported by Baldwin (1995) and Moraes et al (2014) are similar to HE from bond breakage, such as glycogen → glucose, and may only partially represent metabolic processes associated with maintenance. Old and Garrett (1987) described the relationship between RE and MEI as a quadratic function; estimates of ME m were 0.0953 Mcal ME/ BW 0.750 × d −1 (Hereford steers) and 0.100 Mcal ME/BW 0.750 × d −1 (Charolais steers).…”
Section: Variability In K Mmentioning
confidence: 86%
“…For cattle consuming ME such that RE < 0, sources of energy contributing to the total energy economy of the animal are not exclusively ME; for RE > 0 there is a blend of metabolic processes. Baldwin (1995) described k m as ~0.90; Moraes et al, (2014), in a Bayesian framework, used an informed prior, k m = 0.94, similar to that described by Baldwin (1995) and reported a CrI that included 1.0; Moraes et al, (2014) also reported efficiencies greater than 1.0 (CrI = 0.76 to 1.13). Baldwin (1995) and Moraes et al (2014) estimates of k m differ greatly from the efficiency of ATP synthesis.…”
Section: Variability In K Mmentioning
confidence: 99%
See 2 more Smart Citations
“…In their analysis, the inclusion of the molecular breeding value of ribeye area increased by 13% the precision to predict body weight at 28% empty body fat. Despite the development of new concepts for nutrition modeling, revisions of relationships established a long time ago are still needed for three reasons: collection of new data and incorporation with old data (Ellis et al, 2014;Galyean and Tedeschi, 2014); data used to develop past relationships were deemed deficient and/or were based on assumptions that do not hold anymore (Galyean et al, 2016); or more advanced mathematical and/or statistical analyses have been proposed (Moraes et al, 2014a;Moraes et al, 2014b).…”
Section: Integrating Genomics Into Nutrition Modelingmentioning
confidence: 99%